Plastic Deformation of Low Carbon Steels - Monsalve-Gonzalez, A; Artigas-Abuin, A (2012)
The plastic deformation of two steels was studied by means of axisymmetric compression tests carried out in a computer driven servohydraulic machine. The tests were conducted within the temperature range of 700-1100uC for steels that have similar carbon contents, but differed in other alloying elements. Little difference in strength between the steels was found when deformation took place in the austenite phase field, but the strength of the material varied as soon as ferrite was present. The critical temperatures were evaluated by means of thermal analyses, which were conducted by inserting a thermocouple within samples of the two steels; these temperatures were found to be close to those predicted by empirical equations. © 2012 IHTSE Partnership.